The oldest known fur seal - Boessenecker, Robert W. (Biol Lett, 2015)
The poorly known fossil record of fur seals and sea lions (Otariidae) does not reflect their current diversity and widespread abundance. This limited fossil record contrasts with the more complete fossil records of other pinnipeds such as walruses (Odobenidae). The oldest known otariids appear 5–6 Ma after the earliest odobenids, and the remarkably derived craniodental morphology of otariids offers few clues to their early evolutionary history and phylogenetic affinities among pinnipeds. We report a new otariid, Eotaria crypta, from the lower middle Miocene ‘Topanga’ Formation (15–17.1 Ma) of southern California, represented by a partial mandible with well-preserved dentition. Eotaria crypta is geochronologically intermediate between ‘enaliarctine’ stem pinnipedimorphs (16.6–27 Ma) and previously described otariid fossils (7.3–12.5 Ma), as well as morphologically intermediate by retaining an M(2) and a reduced M(1) metaconid cusp and lacking P(2–4) metaconid cusps. Eotaria crypta eliminates the otariid ghost lineage and confirms that otariids evolved from an ‘enaliarctine’-like ancestor.